Luke's Jewish eschatology the National Restoration of Israel in Luke-Acts - Oliver, Isaac W. 1980- (Oxford Oxford University Press USA - OSO, 2021)
This book revisits the Jewish roots of Christianity. More specifically, this work investigates what Luke thought about the Jewish people and the end of time in light of ancient Jewish sources. It is likely that Luke's views on these questions were not too different from the Judaism of Luke's time. Luke believed that Israel would experience political and national restoration when Jesus would return as the victorious messiah.
cover -- Luke's Jewish Eschatology -- Copyright -- Dedication -- Contents -- Acknowledgments -- Abbreviations -- A Note on Transliteration -- 1. Introduction -- Israel's Restoration in Luke-​Acts: Questioning Common Assumptions -- Universalism and Particularism in Luke-​Acts -- Salvation and Nationalism -- Some Remarks on the Date, Authorship, and Audience of Luke-​Acts -- Short Synopsis of This Book -- 2. Israel's National Restoration in Luke's Infancy Narrative -- The Soteriological Vocabulary of Luke's Infancy Narrative -- Universal Salvation and National Restoration in Simeon's Prophecy -- Conclusion -- 3. Jesus Messiah Son of David -- The Infancy Narrative: The Prelude to Jesus's Davidic Messiahship -- The Birth of the Davidic Messiah in Roman Imperial Context -- Baptism as Anointment: The Royal Appointment of Jesus as Davidic King -- The Genealogical Certification of Jesus's Davidic Kingship -- The Restoration of the Davidic Throne -- Conclusion -- 4. Jerusalem and the Restoration of Israel in the Gospel of Luke -- The Mount of Transfiguration (9:28-​36) -- Setting Face Toward Jerusalem (9:51-​56) -- Tragedies in Jerusalem (13:1-​9) -- How Many Will Be Saved? (13:22-​30) -- Lamentation and Hope for Jerusalem (13:31-​35) -- The Parable of the Ten Pounds (19:11-​28) -- Jesus's Entrance into Jerusalem (Luke 19:29-​44) -- Jerusalem Within Luke's Eschatological Discourse (21:5-​36) -- Conclusion -- 5. The Acts of the Apostles and the National Restoration of Israel -- From Jerusalem to Jerusalem -- Apokatastasis -- Pentecost -- The Reunification of the Twelve Tribes -- Luke's Charge Against the Jews for Crucifying Jesus -- Is the End of Acts the End of the Story? -- Conclusion -- 6. Conclusion -- Notes -- Bibliography -- Index of Authors -- Primary Resources -- Subject Index.
Description based on publisher supplied metadata and other sources
Keywords: Kingdom of God-Biblical teaching; Electronic books